Respuesta:
[tex]por \: teorema \: pitagoras \\ {(40)}^{2} + {(x + 1)}^{2} = {(41)}^{2} \\ 1600 + {(x + 1)}^{2} = 1681 \\ (1600 - 1600) + {(x + 1)}^{2}=1681-1600 \\ {(x + 1) }^{2} = {9}^{2} \\ x + 1 = 9 \\ x = 8 \\ piden \\ {x}^{2} + 7 \\ remplazando \\ {8}^{2} + 7 = 71[/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
[tex]por \: teorema \: pitagoras \\ {(40)}^{2} + {(x + 1)}^{2} = {(41)}^{2} \\ 1600 + {(x + 1)}^{2} = 1681 \\ (1600 - 1600) + {(x + 1)}^{2}=1681-1600 \\ {(x + 1) }^{2} = {9}^{2} \\ x + 1 = 9 \\ x = 8 \\ piden \\ {x}^{2} + 7 \\ remplazando \\ {8}^{2} + 7 = 71[/tex]